ALGUNS ELEMENTOS PARA A CONSTRUÇÃO DE UMA HISTÓRIA AMBIENTAL DO PROCESSO DE "EUROPEIZAÇÃO" DA PAISAGEM DO DISTRITO DE ENTRE RIOS, GUARAPUAVA, PARANÁ - Gärtner, Monique (2014)
This dissertation discusses the Europeanization of Entre Rios district`s landscape, in Guarapuava / PR, between 1951 and 1991, from a environmental history perspective in dialogue with the processes of land use transformation in the region. As for research papers, speeches presented in works based on colonization and the regional Swabian literature on immigration were used. We intend to discuss some perceptions of nature environmental and possible consequences in the community development. The research has also tried to understand the justification for the refugees settlement in the district of Entre Rios due to the similarity of this territory to Europe, with the hypothesis that some of the causes of the colonization in Guarapuava has been the regional climate "Europeanization", auspicious to planting also "European" crops such as wheat and barley.